Penggunaan Metode Pembelajaran Discovery Learning Dalam Meningkatkan Pemahaman Siswa Pada Mata Pelajaran Pemeliharaan Sasis Dan Pemindah Tenaga Kendaraan Ringan Di Kelas XI D SMK Negeri 1 Wewewa Barat Tahun Pelajaran 2023/2024 - Mulyono, Yohanis (BULLET : Jurnal Multidisiplin Ilmu, 2024)
This classroom action research aims to evaluate the use of the Discovery Learning method in improving student understanding in the Light Vehicle Chassis and Powertrain Maintenance subject for Class XI D at SMK Negeri 1 Wewewa Barat during the 2023/2024 academic year. The study involved 30 students as research subjects. Data was collected through student scores and the percentage of learning mastery at each cycle: pre-cycle, Cycle I, and Cycle II.  The results showed that in the pre-cycle stage, the majority of students had not achieved mastery, with a non-mastery percentage of 60%. However, after the implementation of the Discovery Learning method in Cycle I, there was a significant improvement. The number of students achieving mastery increased to 19, with the mastery percentage rising to 63.33%.  Following improvements in teaching during Cycle II, there was an even better increase in student understanding. The number of students achieving mastery rose to 27, with the mastery percentage reaching 90%. This indicates the effectiveness of the Discovery Learning method in enhancing students' practical skills. The conclusion of this study is that the use of the Discovery Learning method in teaching the Light Vehicle Chassis and Powertrain Maintenance subject for Class XI at SMK Negeri 1 Wewewa Barat during the 2023/2024 academic year has successfully improved student performance.